The holy waters of En Four: Rituals, prayers, magic and mysticism - Arno M. Meiring (HTS Teologiese Studies/Theological Studies)
Travellers on the N4 highway just east of Pretoria can see evidence of a sacred spring next to the road with pilgrims moving around the landscape and collecting water. This research explored this place – called ‘En Four’ by some – and described visits and conversations had at the site in 2024. The first part of the research narrated the encounters and recorded the local and anecdotal knowledge shared by pilgrims and visitors. The research then analysed the religious significance of the water-based rituals using Rodney Stark’s religion-sociological theory of religion: it identified evidence of magic, prayer, ritual and mysticism. Finally, a number of findings considered the use, value and care of water at this religious site: En Four offers various religious experiences, contributes to mental and physical health and may enhance social cohesion and understanding.